2013
DOI: 10.1063/1.4790279
|View full text |Cite
|
Sign up to set email alerts
|

The growth of microcrystalline silicon oxide thin films studied by in situ plasma diagnostics

Abstract: Influence of plasma-generated negative oxygen ion impingement on magnetron sputtered amorphous SiO2 thin films during growth at low temperatures

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 19 publications
3
29
0
Order By: Relevance
“…20 In addition to the [O]/[Si] ratio dependence of the filament formation, different approaches to tune the crystallinity were investigated, such as the influence of the hydrogen dilution 21 and the PECVD pressure. [22][23][24] Recent studies have also shown that the refractive index and conductivity can be tuned almost independently of each over a wide range. 25 The nanocrystalline silicon growth during PECVD is usually explained by the competition and/or interaction of three distinct mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 In addition to the [O]/[Si] ratio dependence of the filament formation, different approaches to tune the crystallinity were investigated, such as the influence of the hydrogen dilution 21 and the PECVD pressure. [22][23][24] Recent studies have also shown that the refractive index and conductivity can be tuned almost independently of each over a wide range. 25 The nanocrystalline silicon growth during PECVD is usually explained by the competition and/or interaction of three distinct mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, in most of the studies, the crystallinity of nc-SiO x :H was treated as one of several dependent parameters and rarely as the sole subject of investigation. 22 In an earlier publication, 23 the macroscopic nc-SiO x :H film properties, such as Raman crystallinity and refractive index, were correlated with the PECVD process and the plasma properties. In the present work, we unravel the nature of the nc-SiO x :H nanostructure and correlate it to the macroscopic film properties and device behavior in the corresponding solar cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) [13]. Up to six glass substrates of 30×30 cm 2 area were loaded via a load lock to a storage chamber.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the refractive index and the electronic band gap and, thus, the optical absorption of the material can be varied by alloying of the material with carbon and oxygen, e.g. by the admixture of CH 4 or CO 2 to the process gas [9][10][11][12][13]. Due to the a e-mail: onno.gabriel@helmholtz-berlin.de wide spread and large variety of applications of these films the growth mechanism of thin film silicon is the topic of ongoing research.…”
Section: Introductionmentioning
confidence: 99%